Improving the Freight Forwarding Procedure for Containerized Cargo from Tien Sa Port to the Factory at Anh Toan Phat Transport Company Limited - Truong, Quoc Tai (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Logistics and Digital Supply Chain Management; 2021-2025.